Influential Article Review - The Role of Twitter and Trolls in Health Communication - Terry, Corey; Ramos, Evan; Hall, Marcia (Journal of Marketing Development and Competitiveness, 2019)
This paper examines social media. We present insights from a highly influential paper. Here are the highlights from this paper. To understand how Twitter bots and trolls (“bots'') promote online health content. We compared bots’ to average users’ rates of vaccine-relevant messages, which we collected online from July 2014 through September 2017. We estimated the likelihood that users were bots, comparing proportions of polarized and anti vaccine tweets across user types. We conducted a content analysis of a Twitter hashtag associated with Russian troll activity. Whereas bots that spread malware and unsolicited content disseminated anti vaccine messages, Russian trolls promoted discord. Accounts masquerading as legitimate users create false equivalency, eroding public consensus on vaccination. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.